Analisis Kualitas Sumber Daya Manusia pada Sektor Industri dengan Pertumbuhan Tinggi di Indonesia - Annazah, Nur Siti; Martak, Yusuf Faisal; Ilma, Muhammad Alfi Aulia; Munandar, Rezky Aries (Pusat Pengembangan Kebijakan Ketenagakerjaan Kementerian Ketenagakerjaan Republik Indonesia, 2025)
This study addresses the persistent mismatch between sectoral growth and human capital quality in Indonesia. It investigates whether regions experiencing simultaneous economic expansion and improvements in tertiary-educated labor achieve higher wage outcomes. Specifically, it asks: to what extent does the alignment between sectoral development and human capital influence wage growth, and how does training strengthen this effect? Using longitudinal Sakernas data (2012–2022) at the district–sector level and panel regressions with province fixed effects, the analysis assesses wage dynamics based on sectoral shifts, education attainment, and training participation. Findings indicate: (1) only 12.73% of regions are “high–high,” yet they record approximately 74% higher wage levels (around 52% after fixed effects), and (2) education (4–8%) and training (5–7%) individually contribute modest wage gains. Policy implications highlight the need to: (a) integrate human capital strategies with sectoral development planning, and (b) prioritize education and training investments in high-potential sectors to maximize wage outcomes and reduce regional disparities.